2016
DOI: 10.1039/c5en00276a
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of 13C-fullerenol nanomaterials in wheat

Abstract: Fullerenol, an important water-soluble derivative of fullerene carbon nanomaterial, has been increasingly used in medicine and industry. The presence and release of carbon nanoparticles into the environment have raised concerns over potential impacts on human health and the environment. In this study, the bioaccumulation of fullerenol nanoparticles in wheat was investigated using 13 C-labelling techniques. The dose and time-dependent bioaccumulation of fullerenol in wheat was observed, and most fullerenol (abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…She performed the arc discharge experiment and prepared it following the literature protocols. 16,17,19 Briefly, the anode electrode was fabricated by coring out of the 12 C-carbon rods and packing the core with 13 C-enriched amorphous carbon powder (15 wt%). Pure graphite rod was set as the cathode.…”
Section: Preparation Of 13 C-cnpsmentioning
confidence: 99%
See 2 more Smart Citations
“…She performed the arc discharge experiment and prepared it following the literature protocols. 16,17,19 Briefly, the anode electrode was fabricated by coring out of the 12 C-carbon rods and packing the core with 13 C-enriched amorphous carbon powder (15 wt%). Pure graphite rod was set as the cathode.…”
Section: Preparation Of 13 C-cnpsmentioning
confidence: 99%
“…13 In the recent decade, 13 C skeleton isotope labeling of carbon nanomaterials has been established as reliable technique for the quantification of trace amount of carbon nanomaterials in biological systems. [16][17][18][19][20][21] The advantages of 13 C skeleton isotope labeling include high accuracy, low detection limit, nonradioactive nature, high stability, and suitability in long-term tracing. In 2007, we reported that 13 C-carbon nanotubes (CNTs) could be prepared by laser ablation method and quantified by isotope ratio mass spectroscopy (IRMS) in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of [16,47,62] concluded that the positive effect of water-soluble fullerene derivatives on plants is presumably associated with the inhibition of reactive oxygen species (ROS) production. Absorption, translocation, and accumulation of carbon nanomaterials (fullerenes and fullerene derivatives and carbon nanotubes) have been evaluated for the following plants: rice, radish, onion, bitter melon, and wheat [9,57,59,61,63,64].…”
Section: Introductionmentioning
confidence: 99%
“…As an example, authors of [63][64][65] showed that the uptake of C 60 and fullerenol C 60 (OH) 20 by wheat germs (Triticum aestivum L.) and radish (Raphanus sativus L.) depends on their concentration in the root zone, and these compounds were accumulated mainly in the roots. Growthinhibitory effects of another water-soluble derivative, the carboxyfullerene C 70 (C(COOH) 2 ) 2-4 , have been reported in tobacco (N. tabacum) cell cultures, showing cell wall deformations and induction of ROS production [66].…”
Section: Introductionmentioning
confidence: 99%